Checkpoint molecule expression by B and T cell lymphomas in dogs. (30th January 2018) - Hartley, G.; Elmslie, R.; Dow, S.; Guth, A.
Abstract : Immunotherapies targeting checkpoint molecule programmed cell death 1 (PD‐1) protein were shown to be effective for treatment of non‐Hodgkin lymphoma in people, but little is known about the expression of PD‐1 or its ligand PD‐L1 by canine lymphoma. Therefore, flow cytometry was used to analyse expression of PD‐1 and PD‐L1 in canine lymphoma, using fine‐needle aspirates of lymph nodes from 34 dogs with B cell lymphoma (BCL), 6 dogs with T cell lymphoma (TCL) and 11 dogs that had relapsed. Furthermore, fine‐needle aspirates were obtained from 17 healthy dogs for comparison. Lastly, the impact of chemotherapy resistance on expression of PD‐1 and PD‐L1 was assessed in vitro. These studies revealed increased expression of PD‐L1 by malignant B cells compared to normal B cells. In the case of TCL, tumour cells and normal T cells both showed low to negative expression of PD‐1 and PD‐L1. In addition, tumour infiltrating lymphocytes from both BCL and TCL had increased expression of both PD‐1 and PD‐L1 expression compared to B and T cells from lymph nodes of healthy animals. In vitro, chemotherapy‐resistant BCL and TCL cell lines exhibited increases in both PD‐1 and PD‐L1 expression, compared to non‐chemotherapy selected tumour cells. These findings indicate that canine lymphomas exhibit upregulated checkpoint molecule expression, though the impact of checkpoint molecule expression on tumour biological behaviour remains unclear.